Question and answer session 1 : Increasing Engagement with Cultural Heritage Collections - Vézina, Brigitte; van Schaik, Sam; Sanderhoff, Merete; Bailey, Rebecca (British Library, 2021)
Recording of the Question and Answer discussion from Session 1: Increasing engagement with cultural heritage collections. Open and Engaged conference 2021, hosted at the British Library.